'Quite destitute and … very desirous of going to North America': The Roots and Repercussions of Emigration from Sutherland and Caithness. Issue 1 (May 2017) - Harper, Marjory
Abstract : This paper explores the roots and repercussions of emigration from the northern Highlands since the 1770s, through the lens of personal testimony, press accounts, estate papers, and recruitment agents' reports, along with some observations from novels and poetry. It studies the particular exodus from Scotland's two most northerly mainland counties – Sutherland and Caithness – within the wider context of Scottish emigration as a whole, and considers how settlement in Canada, the dominant destination, compares with the experiences of Highland emigrants elsewhere. The investigation has three sections, each of which follows a chronological path. It begins with the practical mechanisms through which emigration was promoted and implemented, and the attitudes that underpinned recruitment and sponsorship. The second section reflects on the attitudes of those who opposed emigration, while the third section dips into the emigrants' own testimony to analyse their motives and experiences. Overarching questions are the extent to which there were unique elements in emigration from the far north; whether the participants were passive victims in a process that was determined by others, or had agency, ambition and agendas of their own; and whether the narrative is characterised by continuity or change during the two centuries under scrutiny.